Legal identification of artificial intelligence in civil proceedings - M. A. Melnichuk; O. N. Savchenko (Гуманитарные и юридические исследования)
Introduction. The study of the role of artificial intelligence and its impact on civil proceedings is an actively researched problem, since its implementation is becoming widespread. Materials and Methods. The research is based on the scientific works of both Russian and foreign scientists. The appeal to the scientific views of specific scientists made it possible to generalize views on the essence of artificial intelligence, to analyze the forms of its use. The study of the issue led to the use of general scientific, logical, comparative legal methods, as well as methods of systematic and complex analysis, which made it possible to comprehensively and fully study the current state of the phenomenon under consideration. Analysis. The study of various scientific developments allows us to talk about the formation of a new scientific and technological environment, the emergence of a new field of legal relations using artificial intelligence technologies. Results. Based on the results of the conducted research, it can be concluded that it is necessary to form special norms of legislation on the creation and use of artificial intelligence. The authors substantiate the need to form a fundamentally new toolkit for the legal regulation of the use of artificial intelligence technologies in legal proceedings, which is associated with the specifics of electronic persons, characterized primarily by difficulties in localizing their legally significant behavior.